Alamat ng ampalaya the legend of the ampalaya - Rivera, Augie D.; Almario, Ani Rosa; Albano, Kora D. (Metro Manila, Filipinas Adarna Books Services, Inc., 1995)
Ito ay isang orihinal na kuwento tungkol sa alamat ng ampalaya. Hinahamon ng kuwento ang haraya ng mga bata, at nagtuturo na rin ng masamang idinudulot ng pagiging maiinggitin at sakim.
This is an original story on the legend of the bitter gourd. It not only challenges the imagination of children; it also teaches the evil of envy and greed.
Text in Filipino and English.
Keywords: Gourds -- Fiction; Children's stories, Filipino; Children's stories, Philippine (English).; Legends -- Philippines -- Fiction